MANY ASPECTS OF THE DIGITAL ECONOMY PROGRAM - Rustamov Dostonbek Jamshid O’g’li (International Journal of Innovations in Engineering Research and Technology, 2021)
The program of the digital economy should provide for the implementation of a number of areas, but one of the main areas - what practical work should be done in the field of education related to the science of digital economy - has not yet been considered.